Model Strategi Evaluasi Program Online Single Submission (OSS) Di Indonesia - Immaculata Yovita Adventy, Maria; Nengyanti; Katriza Imania (Sawala : Jurnal Administrasi Negara, 2024)
This study aims to analyze the evaluation results of the Online Single Submission (OSS) program in Indonesia. A literature review was conducted to identify findings from previous research, indicating several issues such as lack of awareness of business permits, insufficient socialization, complex usability, occasional system errors, and challenges faced by the public in operating the system. The research method employed was descriptive qualitative, utilizing Dunn's theory (Nugroho, 2009: 671) with six indicators: effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy. The evaluation results indicate that the launch of OSS has not been successful and requires improvement to enhance the program. The Strategic Model provides nine recommendations for the OSS program to operate more effectively, namely: Ease of Access (KA), Process Efficiency (EP), Data Security (KD), Customer Service (PP), Quality Improvement (PK), System Integration (KS), User Education (EP), Regulation and Legal Framework (RPH), Monitoring and Evaluation (PE).